Upaya Meningkatkan Perkembangan Kognitif Pada Anak Usia 4-5 Tahun Melalui Alat Permainan Edukatif (APE) Tangram Di PAUD Tunas Muda IKKT - Widiyastuti, Arie; Kasih, Delina; Lestari, Dewi Mutiara (CV. ITTC INDONESIA, 2024)
Dewi Mutiara Lestari. Efforts to improve cognitive development in children aged 4-5 years through the Tangram educational game (APE) at PAUD Tunas Muda (2024). Thesis. Bekasi: Panca Sakti University Bekasi. 2024 This research aims to find out how to improve cognitive development in children aged 4-5 years through the educational game tool (APE) Tangram and to find out whether the educational game tool (APE) Tangram can improve cognitive development in children aged 4-5 years in PAUD Young Shoots. The research method used in this research is a classroom action research model which refers to the Kemmis and MC Taggart classroom action research model, in which there are 4 stages in the research. Namely: Planning, Action, Observation, and Reflection. This research was carried out in 2 cycles to see whether there was an increase in cognitive development in children aged 4-5 years through the Tangram educational game tool (APE) at PAUD Tunas Muda. In the research process, researchers used 2 research instruments. Namely observation and documentation. The subjects of this research were PAUD Tunas Muda IKKT Group A students with a total of 14 children consisting of 5 boys. and 9 daughters. The results of the research show that through the Tangram Educational Game Tool (APE), it can improve cognitive development in children aged 4-5 years at PAUD Tunas Muda. This is shown by the increase in children's cognitive development from pre-action or pre-cycle, namely 42.85%, increasing in Cycle I to 63.69%, and in Cycle II increasing again to 86.90%.